Pemikiran Abdul Karim Soroush dan Implikasinya dalam Kemajuan Pendidikan (Analisis Kritis Distingsi Universitas dan Hawzeh) - Khalim, Ahmad Dwi Nur (Institut Ilmu Al-Qur'an (IIQ) An-Nur Yogyakarta Komplek PP An Nur Ngrukem PO BOX 135 Bantul 55702 Yogyakarta Tlp/Fax (0274) 6469012. http://jurnalannur.ac.id/, 2024)
This study aims to know, analyze and describe the Iranian thinker Abdul Karim Soroush and the implications of his thoughts on university and Hawzeh differences. This is motivated by the concept of Wilayat al-Faqih, the existence of a religious understanding that is immune to criticism and feels absolute. This research is library research. The source of the data was obtained from Abdul Karim Soroush's work Reason, Freedom, and Democracy in Islam: Essential Writings of Abdolkarim Soroush. The data analysis method uses a descriptive method, that is, data is obtained by documentation techniques. Then the descriptive data is analyzed more deeply using content analysis. The results showed that the method of thought used by Soroush in studying religious studies uses epistemological, anthropological and cosmological approaches in which all symptoms are described, explained and normative in one framework. Soroush's thought also states that the problem in the transformation of religious knowledge lies in intellectual self-understanding. There are intellectuals who reject the integration of religious knowledge with other knowledge (negative revivalists) and there are also those who combine religious knowledge with other knowledge (positive revivalists). To mediate these two views, the theory of expansion and narrowing (qabdh wa bast) of religion emerged. Dialogue and integration between religious knowledge and non-religious knowledge will make religious knowledge always contextual in accordance with the development of human knowledge. And these are all special recommendations for Hawzeh.